Breakers, benders, and obeyers: Inquiring into teacher educators’ mediation of edTPA - Ratner, Andrew R.; Kolman, Joni S. (Education Policy Analysis Archives, 2016)
This article reflects a qualitative exploratory inquiry into the lived experiences of faculty members working within a system of urban schools of education as they supported diverse teacher candidates in completing the Educative Teacher Performance Assessment (edTPA) during its first semesters of high-stakes implementation. Drawing upon questionnaire responses and semi-structured interviews, our findings demonstrate the disparity and variation in the level and kind of support offered to teacher candidates. We discuss the ways that the policy, stance, and the ethical, pedagogical, and logistical dilemmas teacher educators faced as they supported candidates intersected to shape the supports provided. Implications focus on utilization of such test scores for evaluating teacher preparation institutions, faculty relations, and the diversification of the teacher workforce.